From Morbidity & Mortality To Textbook Outcomes – The Evolution Of Quality Assessment In Liver Surgery: Perspective From Pakistan - Saleema Begum; Muhammad Rizwan Khan (Journal of the Pakistan Medical Association, 2026)
Traditional quality assessment after liver surgery has focused on individual outcomes, such as morbidity, mortality, length of hospital stay, and readmission rates. Textbook outcomes in liver surgery is a novel concept comprising a composite measure that incorporates multiple perioperative parameters to achieve the most desirable surgical outcomes as a single indicator. It provides holistic perspective and includes multiple facets involving patient care. Liver surgery is a distinct specialty of gastrointestinal surgery, where traditional postoperative outcome tools may not address the hepatectomy-specific complications. Multifaceted care in liver surgery requires specific outcome parameters that can provide procedure specific information to ensure quality assurance and patient safety. Textbook outcome for liver surgery was put together through modified Delphi method between July 2020 and October 2021, and is the established outcome assessment tool. The current review was planned to evaluate the concept of textbook outcome in liver surgery, and discuss its application in the context of Pakistan. Keywords: Liver surgery, Textbook outcomes, Patients safety.